The impact of the online marketplace on fraud: evidence from Craigslist from its early adoption in 1995 to its wider expansion in 2006 - Antonoudi, Efthymia (Kansas State University, 2023)
This research aims to assess the influence of Craigslist’s presence and adoption on fraud arrests within metropolitan statistical areas (MSAs) where it was introduced compared to areas where it was not available. Utilizing the consumer vulnerability framework (Hill & Sharma, 2020), the study used diverse data sources, including Craigslist entry data, the Uniform Crime Reporting (UCR) dataset, and the US Census Bureau Current Population Survey (CPS) data from 1995-2006. Employing differences-in-differences (DID) models, this study's primary findings indicate a reduction in fraud arrests, ranging from 11% to 23% following the introduction of Craigslist. This might appear counterintuitive considering online platforms are sometimes fraud hotspots. However, explanations range from Craigslist’s peer-to-peer transaction format, the existence of a digital trail, platform and community-generated scam education, and an inherent self-policing mechanism where suspicious ads are flagged, reviewed, and removed. While minor frauds may persist and potentially go unreported, Craigslist’s enduring popularity (Oravec, 2014) subjects listings to vast public scrutiny, making large-scale frauds challenging. In collaboration with U.S. law enforcement, Craigslist has introduced safety measures such as posting limitations that deter unsafe activities (Freese, 2011). On the Craigslist website, there is a section that talks about how to avoid scams on the platform (Craigslist, 2023a). Potential extrinsic factors influencing fraud arrests are numerous. Craigslist’s marketplace vitality might present genuine income avenues, reducing fraud incentives. As users become adept at recognizing scams, successful frauds could decline. Additionally, as online platforms become integral in regional economies, law enforcement could foster refined online fraud identification and prosecution tools generating a deterrent effect. Practical implications are discussed and suggestions for future research are provided.
Keywords: Craigslist; Fraud; Fraud arrests; Online marketplace